MAGNETIC FLUX DISTRIBUTION IN SUPERCONDUCTING SINGLE CRYSTALS - Б.И. Хамдамов (Web of Journals Publishing, 2024)
In this work, the simplest model of the critical state of a granular superconductor is studied,which makes it possible to understand the experimentally observed¬ features of the superconductor's behavior in the magnetic fields H > HC1.